The acid dissociation constants of mellitic acid - Adrian Beutler; Anton Stebler (CHIMIA)
The acid dissociation constants of mellitic acid were evaluated at 25 °C from potentiometric titrations in aqueous solutions of the constant Na+ molarity 3 M consisting preponderantly of NaClO4. The obtained values are summarized in the table.